Roberto's Smile - Cowley Joy (Shortland publications)
"Roberto's Smile" is a heartfelt initiative established in memory of Roberto Camacho, a young boy who bravely battled stage 4 diffuse anaplastic Wilms tumor, a rare and aggressive form of kidney cancer. Despite his illness, Roberto was known for his kindness, creativity, and an ever-present smile. He found joy in drawing pictures to uplift others, including doctors, nurses, and fellow patients, embodying a spirit of generosity even during his treatment.